Analisis Pengadaan Bahan Baku Kedelai Pada Industri Rumah Tangga Tahu Dan Tempe (Studi Kasus: UMKM Tahu dan Tempe di Desa Tempurukan, Kabupaten Ketapang) - Nia Ananda Syaputri; Nurimansyah Nurimansyah; Assrorudin Assrorudin; A.Nova Zulfahmi; Rois Indriawan (Jurnal Riset, Inovasi, Teknologi & Terapan, 2026)
Soybeans are the primary raw material in the tofu industry, and their availability significantly affects the smooth operation of micro, small, and medium enterprises (UMKM). This study aims to analyze the raw material procurement system for soybeans at tofu and tempeh processing UMKM in Tempurukan Village, Ketapang Regency, West Kalimantan, using the Economic Order Quantity (EOQ) and Total Inventory Cost (TIC) methods. Data were collected through observation, interviews, and direct documentation at the business locations. The analysis results indicate that the current procurement system, operating at a frequency of 24 times per year, is not yet optimal. The optimal order quantity is 4,243 kg per order with a frequency of 7 times per year, representing a reduction of 70.83% compared to the initial policy. The optimal total inventory cost based on TIC is IDR 2,121,250 per year. In conclusion, the EOQ method has proven effective in optimizing raw material procurement, reducing inventory costs, and ensuring a sustainable supply of raw materials to support the competitiveness of UMKM.